2020
DOI: 10.1002/nau.24373
|View full text |Cite
|
Sign up to set email alerts
|

Medications used to treat bladder disorders may alter effects of neuromodulation

Abstract: Aims Neuromodulation (nerve stimulation) can produce analgesia. One form, bilateral pudendal nerve stimulation (bPNS), suppresses responses to urinary bladder distension (UBD) in hypersensitive rats. Drugs can modify this effect (eg, benzodiazepines, but not opioids, suppress bPNS effects). Prior to a clinical trial of bPNS effects on bladder pain, we felt it was prudent to survey the effects of medications commonly used in patients with bladder disorders. Methods Bladder hypersensitivity was produced by neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…To date, we and others have identified that some of these possibilities have an anatomic and/or physiological basis and may involve subsets of bladder afferents (48,49). For purposes of the present set of studies, it is sufficient to say that various optimal parameters related to NBI treatments have been defined and should be utilized in future studies attempting to delineate the mechanisms of NBI-induced sensitization (50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…To date, we and others have identified that some of these possibilities have an anatomic and/or physiological basis and may involve subsets of bladder afferents (48,49). For purposes of the present set of studies, it is sufficient to say that various optimal parameters related to NBI treatments have been defined and should be utilized in future studies attempting to delineate the mechanisms of NBI-induced sensitization (50)(51)(52)(53)(54).…”
Section: Discussionmentioning
confidence: 99%
“…The clinical application of TNS is potentially limited in patients with alterations of the central nervous pathways including spinal cord, brainstem, and cortical areas due to the demonstrated central nervous interaction. The alertness of the central nervous system might be influenced by specific medications (e.g., antidepressant or other medications with proven central nervous side effects) and thus might influence the processing of afferent and efferent neuronal inputs (e.g., urge to void, voiding, electrical neuromodulation) 14,15 . This shall be addressed and considered in the design of future research.…”
Section: Discussionmentioning
confidence: 99%
“…The alertness of the central nervous system might be influenced by specific medications (e.g., antidepressant or other medications with proven central nervous side effects) and thus might influence the processing of afferent and efferent neuronal inputs (e.g., urge to void, voiding, electrical neuromodulation). 14,15 This shall be addressed and considered in the design of future research.…”
Section: Implication For Clinical Practicementioning
confidence: 99%
“…Used mainly for the treatment of muscle spasticity, it has also found a role in the treatment of neuropathic pain [ 2 4 ]. Recent experiments reported by ourselves [ 5 ] which assessed the effects of commonly employed adjuvant agents on peripheral nerve stimulation-related neuromodulation identified that baclofen may have an analgesic effect on bladder nociception. However, the rats used in those particular experiments had extensive surgeries and received numerous other manipulations.…”
Section: Introductionmentioning
confidence: 99%